Effects of positive psychological capital on entrepreneurial success: A systematic review - Francisco Díaz-Pincheira; Hedy Acosta-Antognoni; Marisa Salanova (Intangible Capital)
Purpose: Psychological resources are key to entrepreneurial performance. Psychological capital is one of the pillars of entrepreneurial success, which has prompted the study of its relationship to entrepreneurial performance. The aim of this study is to contribute to the understanding of the relationship between positive psychological capital and the success of entrepreneurs.